The Moral Evaluation of Living Organ Donation and Trade in Human Organs in Light of Kant’s Ethics (in Polish) - Nowak, Piotr Grzegorz (Diametros, 2015)
In the article I justify the acceptability of ex vivo transplantation and I provide the ethical evaluation of trafficking in human organs from the Kantian perspective. Firstly, I refer to passages of Kant's works, where he explicitly states that depriving oneself of one’s body parts for other purposes than self-preservation is not permitted. I explain that the negative ethical evaluation of the disposal of the body parts was given various justifications by Kant. Subsequently, I provide partial criticism of this justification, resulting in the recognition of the admissibility of ex vivo transplantation. Secondly, I analyse the Kantian slippery-slope argument which, as some philosophers believe, supports banning trade in human organs. It turns out, however, that this argument has wider application, namely it applies to all forms of the instrumental treatment of the human body. Using a previously introduced distinction between organs of the first and the second order, I show that the slippery-slope argument is inconclusive. However, I propose a reinterpretation of this reasoning, which results in using this argument as an additional reason to support prohibiting trade in human organs.